Kajian permasalahan pembelajaran sekolah dasar akibat transisi Kurikulum 2013 ke Kurikulum Merdeka - Habil & Fiona Habil & Fiona (Fakultas Keguruan dan Ilmu Pendidikan Universitas Dharmas Indonesia, 2025)
Curriculum changes in education are an effort to adapt learning to current developments and student needs. The transition from the 2013 Curriculum to the Independent Curriculum brought about changes in learning in elementary schools. This study aims to examine the problems arising from this transition using a qualitative descriptive literature study method. The results of the study indicate that the implementation of the Independent Curriculum still faces various obstacles, such as teacher readiness, student adaptation, limited teaching devices, and assessment implementation. However, the Independent Curriculum also has a positive impact through more flexible, student-centered learning and supports character building. Therefore, teacher training and adequate support facilities are needed for optimal implementation.